Iron Lake : Cork O'Connor #1 - Krueger, William Kent (New York : Atria Paperbacks, 2009)
Part Irish, part Native American, Corcoran "Cork" O'Connor puts aside his grudge against the small Minnesota town that rejected him as a sheriff to investigate a sinister conspiracy responsible for the murder of the local judge.
Keywords: O'Connor, Cork (Fictitious character) -- Fiction; Private investigators -- Minnesota -- Fiction; Minnesota -- Fiction